MRI contrast agents : from molecules to particles - Laurent, Sophie, 1967-; Henoumont, Céline; Stanicki, Dimitri; Boutry, Sébastien; Lipani, Estelle; Belaid, Sarah; Muller, Robert N.; Vander Elst, Luce (Springer Singapore : Imprint : Springer, 2017)
This book describes the multiple aspects of (i) preparation of the magnetic core, (ii) the stabilization with different coatings, (iii) the physico-chemical characterization and (iv) the vectorization to obtain specific nanosystems. Several bio-applications are also presented in this book. In the early days of Magnetic Resonance Imaging (MRI), paramagnetic ions were proposed as contrast agents to enhance the diagnostic quality of MR images. Since then, academic and industrial efforts have been devoted to the development of new and more efficient molecular, supramolecular and nanoparticular systems. Old concepts and theories, like paramagnetic relaxation, were revisited and exploited, leading to new scientific tracks. With their high relaxivity payload, the superparamagnetic nanoparticles are very appealing in the context of molecular imaging but challenges are still numerous: absence of toxicity, specificity, ability to cross the biological barriers, etc.
Keywords: Contrast-enhanced magnetic resonance imaging.; Magnetic resonance imaging.; Molecular biology.; Medical physics.; Radiation.; Nanotechnology.; Biomedical engineering.; Biomedical materials.; elektronické knihy; electronic books